A Review on Heavy Metal Ions and Containing Dyes Removal Through Graphene Oxide‐Based Adsorption Strategies for Textile Wastewater Treatment - Velusamy, Sasireka; Roy, Anurag; Sundaram, Senthilarasu; Kumar Mallick, Tapas (Chemical record, 2021)
Textile wastewater heavy metal pollution has become a severe environmental problem worldwide. Metal ion inclusion in a dye molecule exhibits a bathochromic shift producing deeper but duller shades, which provides excellent colouration. The ejection of a massive volume of wastewater containing heavy metal ions such as Cr (VI), Pb (II), Cd (II) and Zn (II) and metal‐containing dyes are an unavoidable consequence because the textile industry consumes large quantities of water and all these chemicals cannot be combined entirely with fibres during the dyeing process. These high concentrations of chemicals in effluents interfere with the natural water resources, cause severe toxicological implications on the environment with a dramatic impact on human health. This article reviewed the various metal‐containing dye types and their heavy metal ions pollution from entryway to the wastewater, which then briefly explored the effects on human health and the environment. Graphene‐based absorbers, specially graphene oxide (GO) benefits from an ordered structured, high specific surface area, and flexible surface functionalization options, which are indispensable to realize a high performance of heavy metal ion removal. These exceptional adsorption properties of graphene‐based materials support a position of ubiquity in our everyday lives. The collective representation of the textile wastewater‘s effective remediation methods is discussed and focused on the GO‐based adsorption methods. Understanding the critical impact regarding the GO‐based materials established adsorption portfolio for heavy metal ions removal are also discussed. Various heavy‐metal ions and their pollutant effect, ways to remove such heavy metal ions and role of graphene‐based adsorbent including their demand, perspective, limitation, and relative scopes are discussed elaborately in the review. The growing environmental problems caused by toxic heavy metal ions from the industrial textile activities are now the subject of considerable concern for environmental remediation. Graphene oxide and its related compounds envisage emerging solutions to adsorb those pollutant metal ions.